2007
DOI: 10.3171/jns-07/11/0937
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of meningiomas of the cavernous sinus after surgical treatment alone

Abstract: The results suggest that there is no significant oncological benefit in performing surgery within the CS. Because entering the CS entails a significantly higher risk of complications, radiosurgical treatment should be reserved for remnants with secondary growth and clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 51 publications
0
73
1
2
Order By: Relevance
“…Actual tumor growth control rate after GMK of CS meningiomas ranged from 91% to 96.5% at 5 years and 82% to 94% at 10 years (10,12,13,16,23,24,35). In our series, 85.7% patients (12 out of 14 patients) after GMK treatment did not regrow for a mean follow up of 90.6 months and 2 patients had related acceptable complications, including 1 patient had visual deterioration and 1 face hypesthesia on the side of tumor after GMK.…”
Section: Radiosurgerymentioning
confidence: 79%
See 1 more Smart Citation
“…Actual tumor growth control rate after GMK of CS meningiomas ranged from 91% to 96.5% at 5 years and 82% to 94% at 10 years (10,12,13,16,23,24,35). In our series, 85.7% patients (12 out of 14 patients) after GMK treatment did not regrow for a mean follow up of 90.6 months and 2 patients had related acceptable complications, including 1 patient had visual deterioration and 1 face hypesthesia on the side of tumor after GMK.…”
Section: Radiosurgerymentioning
confidence: 79%
“…Al-Mefty(2-4) reported authors (6,9,30-32) proposed a radical and aggressive resection whereas, some authors (5,13,20,21,23,28,35) proposed a conservative strategy with or without following radiosurgery. In our series, total removal was achieved in 104 cases (81.2%), and of 60 cases with CS involvement, 47 were achieved total removal.…”
Section: Neurological Functional Outcomesmentioning
confidence: 99%
“…In one of the largest series to date, de Jesú s et al reported a CSF leak rate of up to 21% when aggressive surgical resection was performed in skull base meningiomas [4]. In two other large series, Sindou et al [6] and Knosp et al [7] reported a trigeminal and visual cranial nerve deficit incidence of between 14 and 58%. Similarly, even with microsurgical resection with intra-operative monitoring, facial nerve dysfunction occurs in up to 7% of patients [26][27][28][29] and hearing loss is universally observed in most acoustic neuromas exceeding 2-3 cm in diameter [30][31][32].…”
Section: Hypofractionatedmentioning
confidence: 96%
“…The most common location for skull base meningiomas is along the sphenoid ridge, followed in frequency by the olfactory grove, the sella/cavernous sinus, the cerebellopontine angle (CPA), the foramen magnum, and around the optic nerve sheath. Approximately 60-75% of skull base meningiomas are considered resectable [4,5]; however, surgical resection is associated with significant morbidity and, in particular, post-operative cranial neuropathy in 14 to 58% of nerves [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, "maximal safe resection" may be a more appropriate strategy than GTR, given the surgical morbidity associated with resection in certain locations (e.g., cavernous sinus). 72,75 Hence, while GTR is the goal, STR may be considered in select patients through traditional open surgery or minimally invasive techniques. 28,36 It is unknown whether STR improves outcomes compared with biopsy alone.…”
Section: Surgical Managementmentioning
confidence: 99%